Analisisis Manajemen Hazard Sisi Jalan Frontage Road Sisi Timur Jalan Ahmad Yani Surabaya: Bahasa Indonesia - Rahayu, Yoanita; Christianto, Melvern Darren (Jurnal Keselamatan Transportasi Jalan (Indonesian Journal of Road Safety), 2024)
Increased activity in a city should be accompanied by the provision of adequate and safe road infrastructure. Ahmad Yani Road has a high accident rate. The problem became important and urgent due to the increasing number of accidents that occured after the construction of the frontage road on Ahmad Yani Road. This study uses a descriptive analysis approach with remote sensing using Google Earth imagery. The road section observed was 3.803 meters long with the analysis boundary on the east side. Results of the analysis carried out, several objects/objects were identified as hazards, including tree branches, iron poles on the right side of the road, and no road boundary lines. Regarding road equipment in the form of markings, signs and delineations, it is well monitored and complete. There is a safety fence that is 15 meters long and has a rigid nature. The fence is made to cover the sewers or pipes so that there are no road accidents in the area.